Legal Discovery in Indonesia’s Tax Dispute Framework - Efendi Ibnususilo; Fithriatus Shalihah; Nisa Istiani; Faiqah Nur Azizah (Journal of Human Rights, Culture and Legal System, 2025)
This study analyzes the normative disharmony among the Tax Court Law, the Judicial Power Law, and the General Provisions and Tax Procedures Law (KUP Law) and examines its implications for the independence and institutional authority of the Tax Court in Indonesia. The inconsistency among these statutory instruments generates juridical uncertainty concerning the structural position of the Tax Court within the national judicial system and obscures the proper framework for institutional oversight. This research aims to assess the existing tax dispute resolution system and to formulate institutional reform proposals through a comparative evaluation of tax adjudication models in the United States, Australia, and Russia. Employing normative legal research, this study applies legislative, conceptual, and comparative approaches to examine statutory coherence and institutional design. The findings demonstrate that, first, dual supervision by the Supreme Court and the Ministry of Finance constrains the structural independence of the Tax Court; second, procedural limitations, including case accumulation, extended adjudication timelines, significant litigation costs, and restricted regional accessibility, reduce the effectiveness of dispute resolution; and third, the absence of a structured Alternative Dispute Resolution framework limits procedural flexibility and institutional responsiveness. Based on these findings, this study argues that placing the Tax Court fully under the authority of the Supreme Court and institutionalizing Alternative Dispute Resolution mechanisms would strengthen judicial independence, improve procedural efficiency, and enhance public confidence in the national tax adjudication system.